2017
DOI: 10.1016/j.ausmj.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Environmental Orientation on Pro-Environmental Purchase Intentions in a Low-Involvement Product Situation

Abstract: Low-involvement consumption includes the majority of regular purchases by individuals and the community, and collectively these have a substantial negative environmental impact. It is, therefore, an important environmental domain to examine. This research surveys 340 Turkish consumers and examines whether apathy, locus of control and myopia influence environmental orientation and purchase intentions for a low-involvement green product, and whether purchase intentions are mediated by consumers’ environmental or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 108 publications
(136 reference statements)
0
16
0
1
Order By: Relevance
“…Consistent with the work of Coşkun et al (2017), the present research takes age, household income, and gender as control variables. Previous scholars (such as Coşkun et al, 2017) have reported a significant association of such variables on exogenous variables related to green buying behavior.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 63%
“…Consistent with the work of Coşkun et al (2017), the present research takes age, household income, and gender as control variables. Previous scholars (such as Coşkun et al, 2017) have reported a significant association of such variables on exogenous variables related to green buying behavior.…”
Section: Literature Review and Development Of Hypothesesmentioning
confidence: 63%
“…Its impact was found as slightly more for high-involved products than low-involved ones. But even if consumers are apathetic, they may have higher intentions to buy pro-environmental products (Coşkun et al, 2017). Therefore, green brand equity is an important indicator of purchase intention even for low-involved green product categories.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The characteristics of "green" consumers (Ginsberg and Bloom, 2004), marketing and brand-related factors such as price, promotions, relevance, perceived quality and brand trust (Weisstein et al, 2014;Hopkins and Roche, 2009) and environmental concerns (Kim and Choi, 2005) affect consumers' intentions to buy green products. In addition to those factors, consumers' intentions and perceptions may vary for low-and high-involvement green products (Coşkun et al, 2017;Atkinson and Rosenthal, 2014).…”
Section: Green Purchasing Intentions and Product Involvementmentioning
confidence: 99%
“…Increases in waste production pose a significant threat to public health and the urban environment especially in developing countries (Dedinec et al , 2015; Vergara et al , 2016). This led to the formulation of various schemes aiming at motivating people to reduce their negative environmental impact (Coşkun et al , 2017) and to research on determinant factors of pro-environmental behavior (Pakpour et al , 2014; Wan et al , 2014; Wang et al , 2018).…”
Section: Introductionmentioning
confidence: 99%